Representation of Gender Stereotyping Resistance Through Instagram Social Media (Critical Discourse Analysis on Instagram @Joviadhiguna) - Dwi Ayu Yulia Sari; Farisha Sestri Musdalifah (Politeknik Negeri Media Kreatif, 2021)
Androgynous groups are a minority group still considered deviant in Indonesia as a person's gender is identified based on appearance. The study was conducted to see how one androgynous individual, Jovi Adhiguna, represented his resistance to gender stereotypes through his Instagram. This qualitative study applies the critical discourse analysis from S.Jager and F.Maier in analyzing the content on @joviadhiguna Instagram account as the data. This study uses Stuart Hall's representation theory. The results showed that Jovi visualized his androgynous style and expressed a resistance form to gender stereotypes in criticism conveyed through Instagram content.